Spatial and temporal attention deficits following brain injury: a neuroanatomical decomposition of the temporal order judgement task. - Roberts, K; Lau, J; Chechlacz, M; Humphreys, G (2012)
We investigated spatial and temporal deficits following brain injury using the temporal order judgement (TOJ) task. Patients judged the order in which two letters appeared to the left and right of fixation. We measured the extent of any spatial bias and the temporal resolution of the decision. Temporal and spatial deficits on the TOJ task were significantly correlated. The spatial bias on the TOJ task was also correlated with the spatial bias on a neglect task and with unilateral deficits on an extinction task, but not with extinction itself. These spatial deficits were all associated with damage to contralateral temporoparietal cortex. In contrast, the temporal resolution of TOJs was linked specifically to deficits in processing multiple stimuli on the neglect and extinction tasks and to damage to the right parietal lobe and the cerebellum. These data suggest that spatial and temporal deficits on the TOJ task reflect different underlying processes.